Alexithymia and self-harm: A review of nonsuicidal self-injury, suicidal ideation, and suicide attempts. (June 2020) - Iskric, Adam; Ceniti, Amanda K.; Bergmans, Yvonne; McInerney, Shane; Rizvi, Sakina J.
Highlights: Consistent evidence demonstrates an association between alexithymia and suicidal ideation, as well as NSSI. Currently, there is inconsistent evidence supporting the association between alexithymia and suicide attempts. The presence of depression may account for significant portion of the relationship between alexithymia and suicidality. However, published data to date had not explicity explored this issue. Abstract: Introduction: Suicide attempts are a significant global public health concern. Research into non-traditional factors, such as the presence of alexithymia, may shed light on the prediction of suicidal behaviours, which can aid intervention and prevention strategies. To ascertain whether alexithymia is a unique risk factor for suicide attempts, this article reviews the evidence on alexithymia related to suicidal ideation, attempts, and non-suicidal self-injury (NSSI). Methods: A literature search was conducted for original articles examining the general and psychiatric populations. Results: There is consistent evidence linking alexithymia with suicidal ideation and NSSI, but inconsistent evidence linking it to suicide attempts. Conclusion: The relationship between alexithymia and suicidality seems to differ based on whether the research focuses on suicidal ideation, suicide attempts, or NSSI. The relationship between alexithymia and suicidality can be understood within the context of multiple code theory and childhood trauma. Future research should explore the whether alexithymia can reliably distinguish between those with a single attempt and those with multiple suicide attempts as well as alexithymia levels pre- and post-intervention with suicide-related behavior as outcomes in treatment studies.